PENGARUH BELAJAR DARING PADA MASA PANDEMI COVID- 19 TERHADAP KEAKTIFAN SISWA PADA SISWA KELAS III UPT SDN 1 WATES - Nungky Kurnia Putri (Lembaga Pengembangan Kinerja Dosen, 2022)
During the current pandemic, effective learning activities that are currently being carried out by all levels of school, whether primary, secondary, or tertiary, are online. The purpose of this study was to describe the effect of learning the online system on student activity during the pandemic in grade III students of UPT SDN 1 Watesn, Pringsewu Regency. This study uses a causal associative quantitative method model. The subjects in this study were grade III elementary school students with 24 students. This study found that there was an effect of online learning on student activity well, because learning was going well and also active students in learning got a significant score of 0.000 <0.05 for a significant level of 5%. the value of tcount is 4,364 while ttable is 2,073 (tcount > ttable) which means that HO for this study is rejected and for Ha is accepted. And based on interviews conducted by researchers, the strategy was carried out by teachers, there is a process carried out by classroom teachers to the process of the current pandemic period, effective learning activities carried out at this time by all levels of schools, both elementary schools, middle schools, and universities are carried out by way in the network (online). The purpose of this study was to describe the effect of learning the online system on student activity during the pandemic in grade III students of UPT SDN 1 Watesn, Pringsewu Regency. This study uses a causal associative quantitative method model. The subjects in this study were grade III elementary school students with 24 students.